Effectiveness of omalizumab in chronic spontaneous urticaria assessed with patient‐reported outcomes: a prospective study. (29th May 2018) - Ghazanfar, M.N.; Holm, J.G.; Thomsen, S.F.
Abstract: Aim: To examine the effectiveness of omalizumab (anti‐IgE) on symptoms and disease‐related quality of life in chronic spontaneous urticaria (CSU) and to identify possible patient‐specific factors associated with response to omalizumab in patients with antihistamine refractory CSU. Methods: Six months prospective trial of omalizumab 300 mg every 4 weeks among patients with CSU from a dermatological university department. The primary outcome was the urticaria activity score in the past week (UAS7) at 3 months. Results: A total of 117 patients (39 men and 78 women) with a mean age of 42 years were included. The mean baseline UAS7 score was 29.3 points (SD = 10.8), which improved to 11.9 points (SD = 12.9) at 3 months follow‐up, difference = 17.4 points (95% CI: 14.8–19.9), P < 0.0001. Other patient‐reported outcomes (PROs) also improved significantly during 3 months of treatment. No significant further improvement was seen between three and 6 months follow‐up. None of the following patient‐specific factors: sex, age, age of onset of CSU, symptom duration, presence of chronic inducible urticaria (CINDU), comorbidities, positive urticaria HR test, smoking, ethnicity, angio‐oedema, serum total IgE level, CRP, leucocytes, absolute neutrophil count or previous treatment with prednisolone or montelukast were significantly associated with response to omalizumab at 3 months, P > 0.05 for all comparisons. Previous treatment with traditional immunosuppressant drugs (azathioprine, cyclosporine or methotrexate) was associated with poorer treatment response to omalizumab at 3 months, P < 0.001. A strong correlation was seen between different patient‐reported outcomes (PROs) at baseline and 3 months follow‐up. Fifteen patients (12.8%) reported side‐effects of the treatment. Conclusion: Omalizumab is a highly effective therapy for antihistamine refractory CSU with treatment effects similar to those observed in randomized controlled trials. Validated PROs to assess disease activity, disease control and impairment of quality of life are valuable tools in the clinical management of CSU. Identification of patient‐specific predictors of effect and safety of omalizumab in CSU is still warranted.